Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Global Internasional Industries Tangerang - Dudung Hadiwijaya; Ahmad Ahmad (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of work motivation and work environment on employee performance at PT. Global International Industries Tangerang. This study uses a quantitative approach. The population in this study are employees at PT. Global International Industries Tangerang with a sample of 65 respondents. Sampling technique by method on probability sampling, with the determination of the sample purposive sampling. Data analysis techniques used are t test, f test and regression.The results of this study indicate that partially work motivation positive and significant effect on performance indicated by the value of tcount> ttable(8,879 > 1.674) and a significant of 0.000. For the work environment partially has a positive and significant effect on performance indicated by tcount> ttable (15,128 > 1.674) and a significant value of 0.000. Simultaneously work motivation and work environment have a positive and significant effect on performance indicated by the value of Fcount> Ftable(131,237 > 3.15) and a significant value of 0.000. The ability of the independent variables of work motivation and work environment to explain the contribution to performance is 80.9% as shown by the R square of 0.809 while the remaining 19.1% is influenced by other factors. With the value of the multiple linear regression equation Y = 2.255 + 0.231X1+0,729X2.